Performance Model of Kulcapi (Karo Musical Instrument) as a Teaching Material in Guitar Learning - Panji Suroso; Adina Sastra Sembiring; Uyuni Widiastuti; Muklis Hasbulah; Bakhrul Khair Amal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study examines performance model of Kulcapi Karo as a teaching material in guitar learning classes at Music Art Study Program in Unimed. To obtain maximum learning outcomes in the learning process, creative strategies and methods are created in utilizing local music culture as a capital in improving music playing skills. Efforts are made in various ways to maximize learning by reviewing and analyzing matters related to the learning process such as; analyze learning objectives, teaching material, strategies or learning methods, including local cultural material as a learning resource that can be adapted to the development and needs of the community in the world of education that continues to grow. Based on this, it is very important if Kulcapi's musical instrument culture as local culture can be packaged and used as teaching material in learning guitar music instruments. This is intended to further enrich students' understanding of theoretical concepts and the practice of playing stringed musical instruments is not only limited to popular knowledge, but also on things that are more specifically including traditional ones. With the effort to study and understand the Kulcapi instrument as teaching material, students must absolutely understand the organology structure and the technique of playing Kulcapi to be able to be developed to the level of being able to play better musical instruments. The technique of playing Kulcapi instrument as a capital in developing students' abilities in guitar courses seems to be more able to improve the achievement of better quality learning outcomes